Modeling the geographic distribution of Myocastor coypus (Mammalia, Rodentia) in Brazil: establishing priority areas for monitoring and an alert about the risk of invasion. (3rd May 2020) - Pereira, Alan Deivid; Pires Adelino, José Ricardo; Garcia, Diego Azevedo Zoccal; Rodrigues Casimiro, Armando Cesar; Vizintim Marques, Ana Carolina; Vidotto-Magnoni, Ana Paula; Bazilio, Sergio; Orsi, Mário Luís
ABSTRACT: Myocastor coypus: is a large semi-aquatic rodent ranked as one of the 100 most invasive species in the world. In Brazil, few ecological studies have been proposed to understand the relationship of this species with the environment. To date, drivers that facilitate its establishment in new areas remain unknown. However, it is generally accepted that the natural distribution of this species is limited to far southern Brazil. The present study aimed to understand the geographic distribution of M. coypus and indicate areas of greater risk of establishment based on bioclimatic predictors and a surveillance map. We observed that M. coypus suitability and risk assessment areas are restricted to the southeastern and southern regions of Brazil and that anthropogenic landscape modifications are an adequate variable to explain the occurrence of the species. Due to the environmental impacts caused by this species, monitoring in environments where it has been introduced is required. The model used herein presented efficient applicability and fit for Brazil. Preventive actions and the management of M. coypus in predicted regions prior to its establishment are recommended.